2003
DOI: 10.1124/jpet.103.053694
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Elevation of Brain-Derived Neurotrophic Factor by Ampakines

Abstract: The ampakine CX614 positively modulates ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor-gated currents and increases brain-derived neurotrophic factor (BDNF) expression. In rat hippocampal slice cultures, CX614 rapidly increases BDNF gene expression but with time, mRNA levels fall despite the continued presence of active drug. The present study examined this apparent refractory period and the possibility that spaced ampakine treatments could sustain elevated BDNF protein levels. In culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 39 publications
5
94
0
1
Order By: Relevance
“…Previous studies by our laboratories indicated that treatment of cultures for 48 h with CX614 decreased AMPAr subunit mRNA and protein levels (Lauterborn et al, 2003). To assess the time course of CX614 on AMPAr protein, cultured slices were incubated with 50 M CX614 for 0, 4, 8, 12, 24, and 48 h (Fig.…”
Section: Treatment Of Cultured Hippocampal Slices With Cx614 Induces mentioning
confidence: 98%
“…Previous studies by our laboratories indicated that treatment of cultures for 48 h with CX614 decreased AMPAr subunit mRNA and protein levels (Lauterborn et al, 2003). To assess the time course of CX614 on AMPAr protein, cultured slices were incubated with 50 M CX614 for 0, 4, 8, 12, 24, and 48 h (Fig.…”
Section: Treatment Of Cultured Hippocampal Slices With Cx614 Induces mentioning
confidence: 98%
“…In addition, antidepressant strategies which do not directly target the monoamine system, such as electroconvulsive shock therapy, transcranial magnetic stimulation, exercise and the novel a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor potentiators and N-methyl-D-aspartic acid (NMDA) antagonists, also increase mRNA or protein BDNF levels in the rat brain. 21,[41][42][43][44][45][46][47][48][49] Although the mechanisms involved in BDNF upregulation remain unknown, SSRI and NARI antidepressants have been reported to increase hippocampal levels of cyclic AMP response binding protein (CREB) in the rat, a nuclear transcription factor known to regulate BDNF expression. 32 …”
Section: Preclinical Evidencementioning
confidence: 99%
“…Human BDNF and TrkB expression are decreased in depressed patients Post-mortem hippocampal mRNA and protein 49 Serum protein from living patients [51][52][53]56 BDNF levels are increased in patients receiving pharmacological antidepressants Post-mortem hippocampal protein 48 Serum protein from living patients [53][54][55][56] BDNF levels refer to mRNA apart from where specified. Abbreviations: AMPA, a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid; BDNF, brain-derived neurotrophic factor; ECS, electroconvulsive shock; MAOi, monoamine oxidase inhibitor; NARI, noradrenalin reuptake inhibitor; NMDA, N-methyl-D-aspartic acid; SNRI, serotonin and noradrenalin reuptake inhibitor; SSRI, selective serotonin reuptake inhibitor; TMS, transcranial magnetic stimulation; TrkB, tyrosine kinase receptor B; VTA, ventral tegmental area.…”
Section: Midbrain 27mentioning
confidence: 99%
“…They have been associated with enhanced neurogenesis 228 and increased expression of neurotrophic factors such as BDNF. 229,230 The AMPAkine Ampalex exhibited more rapid effect (during the first week of treatment) than fluoxetine (after 2 weeks). 231 Metabotropic glutamate receptors.…”
Section: Glutamatergic Strategiesmentioning
confidence: 99%